Functionalized gold nanoparticles for drug delivery - Sandra Rocha (2013)
Gold nanoparticles are versatile vectors for biological applications including in cancer therapy and diagnosis. Combining gold nanoparticles/anticancer drugs with X-rays radiation may contribute to tumor eradication and treatment efficacy. The conjugation of a proteasome inhibitor (BTZ) with functionalized gold nanoparticles were tested. The drug activity and the anticancer effects in human prostate cancer cells (Du-145) were evaluated. It was observed that gold nanoparticles, with small diameters (24 nm), at concentrations of 0.1 nM are not toxic for Du-145 cells. Finally, nanoparticle parameters were discussed and new ideas are proposed to optimize the anticancer properties of conjugated gold nanoparticles leading to a better delivery of the drug, minimizing the side effects.